Relationship between DIAGNOdent values and sealant penetration depth on occlusal fissures - Rodrigues, Jonas A.; Diniz, Michele B. [UNESP]; Hug, Isabel; Cordeiro, Rita C. L. [UNESP]; Lussi, Adrian (Springer Heidelberg, 2010)
The aim of this in vitro study was to evaluate the relationship between laser fluorescence values and sealant penetration depth on occlusal fissures. One hundred and sixty-six permanent molars were selected and divided into four groups, which were each treated using a different sealant (two clear and two opaque). The teeth were independently measured twice by two experienced dentists using two laser fluorescence devices-DIAGNOdent (LF and LFpen)-before and after sealing, and then thermoclycled. After measuring, the teeth were histologically prepared and assessed for caries extension. Digital photographs of the cut sealed sites were assessed, and the sealant penetration depth was measured. All 166 sites were measured by one of the examiners taking as limits the outer and inner surface of the sealant into the fissure. For each device (LF and LFpen) and each group, the difference between the values at baseline and after sealing was plotted against the sealant penetration depth and scatter plots were provided. It could be observed that most of the points were concentrated around the zero line, for both LF and LFpen in the four groups. In conclusion, there is no relation between changes in DIAGNOdent values and increasing of depth sealant penetration within the occlusal fissures.
Keywords: Dental caries; Detection; DIAGNOdent; Laser fluorescence; Occlusal sealants; Teeth